Di, At Proses Penyelesaian Sengketa Perbuatan Melawan Hukum Oleh Penguasa Melalui Pengadilan Tata Usaha Negara di Indonesia - Tino Adiantomo, Yulius; Asael, Muhammad; Miswadi, Robin Krisna; Rachman, Shofwan (Faculty of Law Universitas Lancang Kuning, 2023)
In carrying out governmental tasks, government officials or agencies are given broad authority in accordance with the proportion of their positions. This broad authority allows for abuse of authority, so that on the part of the community, forms of loss arise in the form of injustice, which is certainly contrary to applicable law. This is often referred to as an unlawful act by the authorities, which in Dutch means onrechmathige daad, so to avoid this, another institution is needed to control the government implementing agency. The Indonesian state adheres to the theory of trias politica in which the executive branch is controlled by equal institutions, namely the legislature and the judiciary. In carrying out state duties, the executive branch is controlled by a judiciary, namely the State Administrative Court (PTUN). In this case, it is necessary to know regarding the role of the TUN Judiciary, namely the implementation of state administration such as the termination of disputes carried out by individuals or civil bodies against officials or government agencies that arise because of the issuance of TUN Decisions and law enforcement in an act against the law by the authorities effectively and efficient